Development of Remdesivir as a Dry Powder for Inhalation by Thin Film Freezing - Sawittree Sahakijpijarn; Chaeho Moon; John J. Koleng; Dale J. Christensen; Robert O. Williams (MDPI AG, 2020)
Remdesivir exhibits in vitro activity against SARS-CoV-2 and was granted approval for emergency use. To maximize delivery to the lungs, we formulated remdesivir as a dry powder for inhalation using thin film freezing (TFF). TFF produces brittle matrix nanostructured aggregates that are sheared into respirable low-density microparticles upon aerosolization from a passive dry powder inhaler. In vitro aerodynamic testing demonstrated that drug loading and excipient type affected the aerosol performance of remdesivir. Remdesivir combined with optimal excipients exhibited desirable aerosol performance (up to 93.0% FPF< 5 µm; 0.82 µm mass median aerodynamic diameter). Remdesivir was amorphous after the TFF process, which benefitted drug dissolution in simulated lung fluid. TFF remdesivir formulations are stable after one month of storage at 25 °C/60% relative humidity. An in vivo pharmacokinetic evaluation showed that TFF remdesivir-leucine was poorly absorbed into systemic circulation while TFF remdesivir-Captisol® demonstrated increased systemic uptake compared to leucine. Remdesivir was hydrolyzed to the nucleoside analog GS-441524 in the lung, and levels of GS-441524 were greater in the lung with leucine formulation compared to Captisol®. In conclusion, TFF technology produces high-potency remdesivir dry powder formulations for inhalation that are suitable to treat patients with COVID-19 on an outpatient basis and earlier in the disease course where effective antiviral therapy can reduce related morbidity and mortality.